2001
DOI: 10.1063/1.1359766
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of pulsating turbulent channel flow

Abstract: Direct and large-eddy simulations of the Navier-Stokes equations are used to study the pulsating flow in a channel. The cases examined span a wide range of frequencies of the driving pressure gradient, and encompass different physical behaviors, from the quasi-Stokes flow observed at high frequencies, to a quasisteady behavior at the lowest ones. The validity of the dynamic Smagorinsky model to study this kind of unsteady flow is established by a posteriori comparison with direct simulations and experimental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
172
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(195 citation statements)
references
References 49 publications
21
172
0
2
Order By: Relevance
“…The domain dimensions are set to l x ϫ l y ϫ h =4ϫ 2 ϫ 1, which is comparable to the one used by Scotti and Piomelli. 7 The largest correlation scale in the velocity field we observe in the simulations is about 0.3, i.e., much smaller than the horizontal domain dimensions.…”
Section: Numerical Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The domain dimensions are set to l x ϫ l y ϫ h =4ϫ 2 ϫ 1, which is comparable to the one used by Scotti and Piomelli. 7 The largest correlation scale in the velocity field we observe in the simulations is about 0.3, i.e., much smaller than the horizontal domain dimensions.…”
Section: Numerical Setupmentioning
confidence: 99%
“…Several studies revealed that LES can be used for oscillating wall flows. 7,14 Nonetheless, we will also perform DNS for our specific flow problem, as in none of those studies a freesurface stress was applied in combination with an oscillatory forcing. In LES only the dynamics of the large scales in the flow are calculated directly.…”
Section: Numerical Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…The propagation starts at Re D = 21000 or ξ = 10, so the propagation velocity based on Re D = 21000 is about c + = 0.7. It is interesting to note that the new turbulence structures propagated at a constant speed in the acceleration phase of the pulsating turbulent channel flow (Scotti and Piomelli, 2001). At low pulsating frequencies, the propagation speed in the pulsating flow was c + = 2κ, where κ is the von Karman constant.…”
Section: Time Delaymentioning
confidence: 99%
“…There are extensive studies of periodic flows around a non-zero mean, and oscillatory flows around zero mean flows. Readers interested in those topics are referred to recent studies of Scotti & Piomelli (2001), Tardu & Da Costa (2005), He & Jackson (2009) and Manna, Vacca & Verzicco (2012) for pulsating flows and Fornarelli & Vittori (2009) and Van der A et al (2011) for oscillatory flows.…”
mentioning
confidence: 99%